Chemical Quality of Synbiotic Yogurt using Lactobacillus bulgaricus as Probiotics With Mulu Bebe Banana Puree - Yusnaini B. Talebe; Sri Lestari (Agrikan: Jurnal Agribisnis Perikanan, 2020)
This study aimed to evaluate the best formulation based on the ratios of Mulu Bebe banana puree on synbiotic yogurt. This study used 10% Lactobacillus bulgaricus lactic acid and mulu bebe banana puree incorporated into liquid milk, with the ratios (banana puree to liquid milk) of 1: 0.25; 1: 0.5; 1: 0.75, and 1: 1. Analysis of synbiotic yogurt focused on chemical properties, including moisture, ash, protein, fat, and carbohydrate. The data analysis was subjected to one-way ANOVA in a Completely Randomized Design (CRD) with 3 (three) replications. The result showed that the synbiotic yogurt using L. bulgaricus probiotics and different volumes of mulu bebe banana prebiotic meet the SNI 2981: 2009 requirements for nonfat yogurt, namely a maximum fat content of 0.5%, a minimum protein of 2.7%, and an optimum ash content of 1, 0%. Regarding quality, the best yogurt in this study contained 10% probiotics and 2.5% mulu bebe banana pure prebiotic.